2019
DOI: 10.3390/pr7090628
|View full text |Cite
|
Sign up to set email alerts
|

Finite Element Simulation of Multiple Slip Effects on MHD Unsteady Maxwell Nanofluid Flow over a Permeable Stretching Sheet with Radiation and Thermo-Diffusion in the Presence of Chemical Reaction

Abstract: The aim of the present study is to investigate the multiple slip effects on magnetohydrodynamic unsteady Maxwell nanofluid flow over a permeable stretching sheet with thermal radiation and thermo-diffusion in the presence of chemical reaction. The governing nonlinear partial differential equations are transformed into a system of coupled nonlinear ordinary differential equations with the aid of appropriate similarity variables, and the transformed equations are then solved numerically by using a variational fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 81 publications
(47 citation statements)
references
References 50 publications
2
39
0
Order By: Relevance
“…The results that have acquired by FEM are a good consensus, which avows the legality of FEM, clearly observed in Table 3. In Table 4, the skin friction coefficient − f (0) obtained by FEM and is also compared with the numerical results of Bagh et al [39] and exact solution of Mudassar et al [40], when all other parameters are supposed to be zero. An excellent correlation has been achieved and grid invariance test has been conducted to maintain four decimal point accuracy.…”
Section: X1 X2 X3 X4 Xpmentioning
confidence: 99%
“…The results that have acquired by FEM are a good consensus, which avows the legality of FEM, clearly observed in Table 3. In Table 4, the skin friction coefficient − f (0) obtained by FEM and is also compared with the numerical results of Bagh et al [39] and exact solution of Mudassar et al [40], when all other parameters are supposed to be zero. An excellent correlation has been achieved and grid invariance test has been conducted to maintain four decimal point accuracy.…”
Section: X1 X2 X3 X4 Xpmentioning
confidence: 99%
“…Our results have decent agreement with the published results that declare the legitimacy of the finite element method and is shown in Tables 3 and 4. Table 3 shows the consequences of the heat transfer proportion, which is assimilated through the finite element method and is associated through the results of earlier studies and with the exact solutions of [38][39][40][41]. To ensure the accuracy of the existing precise values, the conclusions attained by the finite element method for the Nusselt number, the steady flow and the computed results that are stated in earlier studies are shown in Table 3.…”
Section: Resultsmentioning
confidence: 99%
“…This section was prepared to inspect the presentation of the dimensionless axial velocity profilẽ f (ξ), and the temperature distributionθ(ξ) together with the concentration profileφ(ξ) , under the influence of different emerging parameters such as the viscosity parameter λ, Hartman number M, Grashof number Gr, thermophoresis parameter Nt, Brownian motion parameter Nb, Lewis number Le, and Prandtl number Pr as shown in all the graphs. Furthermore, the acquired results of Skin friction and the Nusselt number were compared with the existing results of [42][43][44][45] and presented in the form of tables. Moreover, all the other using parameters are preserved to be fixed throughout the problem as Pr = M = λ 1 = 1, S 1 = 0.2, Le = 1, Nb = Nt = 0.1, S 2 = 0.2, α T = 0.05, λ 2 = 0.09.…”
Section: Resultsmentioning
confidence: 99%
“…The aspect of the existing outputs and assessment of skin friction was done with accurate results that confirm the legitimacy of the finite element technique. Table 2 shows the results of heat transference proportion which were assimilated through the finite element technique and are compared with the results of previous studies as well as with the exact solutions of [42][43][44]. To ensure the accuracy of the current precise values, the conclusions attained by the finite element method for the Nusselt number for the unsteady and steady flow were compared with the calculated results from earlier studies, are shown in Table 3, which shows the current results, that is, creditable conventionality supported by current results and earlier available research that approves the intensity and exactness of the current results that were attained by the finite element method (FEM).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation